2021
DOI: 10.1111/fare.12587
|View full text |Cite
|
Sign up to set email alerts
|

Bills, babies, and (language) barriers: Associations among economic strain, parenting, and primary language during the newborn period

Abstract: The goal of this study was to examine associations among economic strain, parenting self-efficacy, parenting satisfaction, and parent primary language in a universally low-income sample of parents with newborns. Background: Previous research links increased economic strain to lower levels of parenting self-efficacy and parenting satisfaction among socioeconomically diverse parents with older children. Little research has examined whether primary language shapes the associations among economic strain, parenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Studies have reported several adverse effects of financial hardship on different members of the family system. Among adults, financial hardship has been found to contribute to caregiver depression [11,12], increased psychological distress [41], relational conflicts [14], decreased self-efficacy [13], increased aggression [42], and reduced positive parenting techniques [12,14]. The heightened stress experienced by caregivers facing financial hardship can affect their behaviors, parenting satisfaction, and, ultimately, their ability to engage in sensitive parenting [13,43,44].…”
Section: Financial Hardship and Adverse Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported several adverse effects of financial hardship on different members of the family system. Among adults, financial hardship has been found to contribute to caregiver depression [11,12], increased psychological distress [41], relational conflicts [14], decreased self-efficacy [13], increased aggression [42], and reduced positive parenting techniques [12,14]. The heightened stress experienced by caregivers facing financial hardship can affect their behaviors, parenting satisfaction, and, ultimately, their ability to engage in sensitive parenting [13,43,44].…”
Section: Financial Hardship and Adverse Outcomesmentioning
confidence: 99%
“…Among adults, financial hardship has been found to contribute to caregiver depression [11,12], increased psychological distress [41], relational conflicts [14], decreased self-efficacy [13], increased aggression [42], and reduced positive parenting techniques [12,14]. The heightened stress experienced by caregivers facing financial hardship can affect their behaviors, parenting satisfaction, and, ultimately, their ability to engage in sensitive parenting [13,43,44]. Preoccupation with addressing pressing family economic needs affects a caregiver's ability to fully invest in the long-term social, health, and educational needs of a child in their care [45].…”
Section: Financial Hardship and Adverse Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial concerns also influence parents’ attitudes and behaviours associated with parenting, impacting their capacities to interact positively with their families [ 17 ]. Negative associations between economic strain, parental self-efficacy, and parental satisfaction have been documented [ 9 , 18 , 19 ]. Financial difficulties can affect the relationship quality between parents and children [ 20 ], and parental mental health, including depression and anxiety, can contribute to a deterioration of positive parenting practices [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%